Optimalisasi Program Simpan Pinjam pada Badan Usaha Milik Desa (BUMDes) untuk Mewujudkan Kemandirian Ekonomi Masyarakat Desa Kalimanah Kulon (Dharma Ekonomi, 2026)
The presence of BUMDes is an important factor in improving the economy and community independence, such as through the village savings and loan program. However, the lack of socialization and inaccurate targeting of program recipients are problems that have implications for BUMDes capital turnover. This study aims to explain the optimization of the savings and loan program in BUMDes in realizing the economic independence of the community of Kalimanah Kulon Village, Kalimanah District, Purbalingga Regency. This study uses a qualitative case-study approach. Data were obtained through interviews, observations, and document analysis. The results show that the BUMDes savings and loan program is able to increase village income and community welfare, although it is still not optimal. In its implementation, there are several obstacles that have the potential to hinder the implementation of this program, including the issue of inadequate human resources, minimal business planning and innovation, and low community participation in loan repayment and BUMDes business management. Therefore, adequate planning by the village government to increase the capacity of managers and community participation, as well as strengthening institutions and collaboration with relevant stakeholders in BUMDes business management are important prerequisites for optimal program achievement. In addition, intensive and ongoing outreach to all levels of society regarding BUMDes programs is needed to ensure BUMDes can more optimally fulfill their role in improving village welfare and independence.